Clinical and radiographic comparison of indirect pulp treatment using light-cured calcium silicate and mineral trioxide aggregate in primary molars: A randomized clinical trial - Navya P Menon; Balagopal R Varma; Sureshkumar Janardhanan; Parvathy Kumaran; Arun Mamachan Xavier; Bhat Sangeetha Govinda (Wolters Kluwer Medknow Publications, 2016)
Aim: To clinically and radiographically evaluate the reparative dentin formation in indirect pulp treatment (IPT) using mineral trioxide aggregate (MTA) and light cured calcium silicate (TheraCal) in primary molars over a period of 6 months. Materials and Methods: A clinical trial on IPT on 43 primary molars in 21 patients between the age of 4-7 years, divided into two groups: 22 teeth in MTA group and 21 in TheraCal group. Measurement of the variation in dentin thickness was done on the digitalized radiograph at baseline, 3 months and 6 months using CorelDRAW X3 software. Results: Statistical analysis using an independent t-test for intragroup and intergroup comparison showed a significant increase in dentin thickness in both the MTA and TheraCal group (intragroup comparison [P < 0.05]). However, intergroup comparison between MTA and TheraCal showed no statistical difference in reparative dentin formation (P > 0.05). Conclusion: Clinically and radiographically, both MTA and TheraCal are good IPT materials. The better handling characteristics and comparable reparative dentin-forming ability of TheraCal make this material an alternative to MTA in pediatric restorative procedures.